ARTIKEL REVIEW: AKTIVITAS ANTIBAKTERI EKSTRAK DAUN KARAMUNTING (Rhodomyrtus tomentosa) TERHADAP BAKTERI PATOGEN - Rahmi Mulyani, Shifa (Jurnal Biogenerasi, 2026)
Infectious diseases caused by pathogenic bacteria remain a health concern, particularly due to increasing antibiotic resistance. Natural products such as karamunting leaves (Rhodomyrtus tomentosa) have potential as alternative antibacterial agents. This review aims to evaluate the antibacterial activity of karamunting leaf extracts against pathogenic bacteria through a literature review. Relevant scientific articles were analyzed. The results show that karamunting leaf extracts inhibit the growth of Escherichia coli, Staphylococcus aureus, Salmonella typhi, and Streptococcus mutans, as indicated by the formation of inhibition zones with varying diameters. Differences in antibacterial activity are influenced by extract concentration, bacterial species, testing methods, and secondary metabolite content. These findings indicate that karamunting leaf extracts have potential as natural antibacterial agents.